Ganoderma lucidum Modulates Glucose, Lipid Peroxidation and Hepatic Metabolism in Streptozotocin-Induced Diabetic Pregnant Rats - Viroel, Fabia Judice Marques; Laurino, Leticia Favara; Caetano, Érika Leão Ajala; Jozala, Angela Faustino; Spim, Sara Rosicler Vieira; Pickler, Thaisa Borim; Sercundes, Michelle Klein; Gomes, Marcela C. [UNESP]; Hataka, Alessandre [UNESP]; Grotto, Denise; Gerenutti, Marli (MDPI, 2022)
The consumption of functional foods, such as mushrooms, apparently influences Gestational Diabetes Mellitus (GDM), and brings benefits to maternal-fetal health. Ganoderma lucidum contains a variety of bioactive compounds, such as polysaccharides, proteins and polyphenols that are able to control blood glucose and be used in anti-cancer therapy. We aimed to evaluate the effects of the consumption of Ganoderma lucidum (Gl) on maternal-fetal outcomes in streptozotocin-induced GDM (GDM-STZ). Pregnant rats were exposed to Gl (100 mg/kg/day) before and after the induction of GDM-STZ (single dose 40 mg/kg) on the eighth pregnancy day. Biochemical and oxidative stress parameters, reproductive performance and morphometry of fetuses were assessed. Gl reduced the glycemic response in the oral glucose tolerance test. Moreover, Gl decreased AST and ALT activities. GDM increased lipid peroxidation, which was reverted by Gl. Catalase and glutathione peroxidase activities were decreased in GDM and the administered Gl after the fetus implantation increased catalase activity. Measurements of the fetal head, thorax, craniocaudal and tail showed greater values in fetuses from rats exposed to Gl compared to GDM. Ganoderma lucidum has an encouraging nutritional and medicinal potential against GDM, since it modifies glucose metabolism, reduces lipid peroxidation, and has protective effects in fetuses born from GDM dams.
Keywords: Ganoderma lucidum; Gestational Diabetes Mellitus; glucose; oxidative stress; rat